Ill fares the land - Judt, Tony. (Penguin Books, 2010)
In "Ill Fares The Land," Tony Judt, one of our leading historians and thinkers, reveals how we have arrived at our present dangerously confused moment and offers the language we need to address our common needs, rejecting the nihilistic individualism of the far right and the debunked socialism of the past. To find a way forward, Judt argues that we must look to our not so distant past and to social democracy in action: to re-enshrining fairness over mere efficiency.